127 A Student Pilot For A Feasibility Study of the Theoretical 3S Trial (SPFT3S): Patient Questionnaire and Demographics. (16th March 2021) - Foster, R; Dodd, M; Brown, L; Awonaya, K; McCormack, T
Abstract: Introduction: There is conflicting evidence on the benefit of statins for primary prevention of cardiovascular disease (CVD) in non-diabetics over 75. Emerging evidence shows they may be ineffective, yet current guidance supports their use in those up to 85. The objectives of this study were to assess patients' understanding of statins, willingness to participate in a theoretical randomised controlled trial (RCT), where they would be randomised to stop their statin and to compare the trial population with national data. Methods: The survey took place in 8 GP practices with 4 students involved in questionnaire distribution. A patient search identified those over 75 and on a statin. Patients were excluded if they had a history of CVD or diabetes. 36 patients were identified and completed questionnaires, 5 were removed because they reported exclusion criteria. Demographic data was compared to the UK population from the 2011 census. Results: Of 31 participants, 71% understood why they took statins, most were unconcerned about side effects and only 1 patient stopped statins due to the media. Opinions on the theoretical "stopping statins trial" were varied. 35% of people responded positively. 29% would not want to take part and 36% of people were unsure. Comparison of our trial population against the national population shows that 903, 505 people would be eligible for a UK trial. Conclusions: The purpose of this exercise was to see if patients would be willing to participate in a trial where 50% stopped taking their statin. Approximately a third said yes and only a third said no. As there are nearly a million people in this population, it suggests a fully funded, larger-scale feasibility study of this theoretical randomised control trial is warranted.